Production information interoperability over the Internet: A standardised data acquisition tool developed for industrial enterprises - Cutting-Decelle, A.; Barraud, J.; Veenendaal, Bert; Young, R. (Elsevier BV, 2012)
The data acquisition process in a shop floor collects data at the shop floor level, it then provides their identification and their content before their provision to the manufacturing management level. Those data may address: equipments, batches, products or the staff. They are requested for the KPI calculations, for the manufacturing and quality monitoring and for the improvement of manufacturing operations. They also enable the validation of shop floor models and scheduling scenario. The objective of this paper is to present a real example of a data acquisition system based on a standardised data model, the model being provided by the ISO 15531-44 standard. The system described in this paper is under development and it has already been tested in several plants of the Schneider Electric Sensors company with a great success. We will present in this paper the methodology used, together with results available today, but also the perspectives offered by the approach. Â© 2012 Elsevier B.V. All rights reserved.